The Influence of Twitter Social Media Usage on Student Behavior: A Case Study of 'Alone Together' - Syalaisha Nabila; Ciello Alvanda Laurend; Eliya Kurniawati (Cakra Communico: Journal of Communication Science, 2024)
Social media has become an integral part of teenagers' lives in this digital era. In this context, this study aims to measure the extent of the influence of social media on the behavior of teenagers who often experience the phenomenon of "Alone Together." To explore a deeper understanding of the relationship between social media and teenage behavior, this study refers to Dependency Theory. To explore a deeper understanding of the relationship between social media and teenagers' "Alone Together" behavior, this study refers to Dependency Theory. This theory will be the framework used to analyze how adolescents depend on social media, the extent to which this dependence affects their social interactions, and whether this contributes to the "Alone Together" phenomenon. This research has important significance in understanding the implications of social media use on adolescents' well-being as well as providing a more comprehensive view of how communication in the digital world affects the social dynamics of the younger generation. The method used in this research is a survey, which will be conducted by sending questionnaires to the research subjects, especially in the group of teenage students. This survey will help us to collect the necessary data to measure the extent of the influence of social media on "Alone Together" behavior among teenagers. The selection of research subjects in the teenage group, especially university students is considered relevant because at that age they are active users of social media and have an important role in today's social dynamics. This quantitative research will be conducted in the city of Malang. The main result that will be measured in this study is the level of influence of social media on "Alone Together" behavior in adolescents. Thus, this study is expected to provide a deeper insight into the relationship between social media and the phenomenon of "Alone Together," the variable observed in this study is how social media influences the behavioral changes that occur to college students. conclusion through the application of Dependency Theory, this study aims to reveal the extent to which social media dependency affects the phenomenon of "alone together" among adolescents, especially college students.